Impact of social compliance on employee motivation: An empirical evaluation - Alam M.N.; Alias R.B.; Hassan M.D.M. (Mattingley Publishing, 2023)
Motivation; Wages; Discrimination; Employee motivation; Harassment; Leave; Social compliance; Welfare; Garment industry